An introduction to multivariate statistical analysis - Anderson, T. W. ([S.l.] : Wiley-Interscience, 2011)
Perfected over three editions and more than forty years, this field- and classroom-tested reference: * Uses the method of maximum likelihood to a large extent to ensure reasonable, and in some cases optimal procedures. * Treats all the basic and important topics in multivariate statistics. * Adds two new chapters, along with a number of new sections. * Provides the most methodical, up-to-date information on MV statistics available.
Keywords: Multivariate analysis